2011
DOI: 10.3851/imp1716
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for a New Mechanism of Inhibition of H I V-1 Integrase Identified by Fragment Screening and Structure-Based Design

Abstract: Background: HIV-1 integrase is a clinically validated therapeutic target for the treatment of HIV-1 infection, with one approved therapeutic currently on the market. This enzyme represents an attractive target for the development of new inhibitors to HIV-1 that are effective against the current resistance mutations. Methods: A fragment-based screening method employing surface plasmon resonance and NMR was initially used to detect interactions between integrase and fragments. The binding sites of the fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 46 publications
0
43
0
Order By: Relevance
“…HIV-IN has been proven to be a clinically valid target; however, resistance to inhibition by active-site inhibitors, including raltegravir (Isentress), has been observed to be rapid in the clinic even in the presence of optimised, highly active antiretroviral therapy (HAART) regimens. [1] Therefore, other strategies for inhibiting the essential integration process are being considered and include the targeting of novel pockets [2] and blocking the interactions of the host cofactor cell lens epithelium-derived growth factor (LEDGF, also known as p75) with HIV-IN. [3][4][5] Several viral and host cofactors have been identified that regulate the function of HIV-IN as part of the preintegration complex (PIC).…”
Section: Introductionmentioning
confidence: 99%
“…HIV-IN has been proven to be a clinically valid target; however, resistance to inhibition by active-site inhibitors, including raltegravir (Isentress), has been observed to be rapid in the clinic even in the presence of optimised, highly active antiretroviral therapy (HAART) regimens. [1] Therefore, other strategies for inhibiting the essential integration process are being considered and include the targeting of novel pockets [2] and blocking the interactions of the host cofactor cell lens epithelium-derived growth factor (LEDGF, also known as p75) with HIV-IN. [3][4][5] Several viral and host cofactors have been identified that regulate the function of HIV-IN as part of the preintegration complex (PIC).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been a steady release of high-resolution IN CCD cocrystal structures containing small molecules or fragments derived from SPR and STD-NMR fragment-based screens. These ligands bind various pockets on the IN surface and delineate local pharmacophoric features [12][13][14]. Although binding to some of these sites has not yet been shown to interfere with IN activity (either directly or indirectly), the conserved nature and pleiotropic effects associated with these sites together with the data support strategies to develop novel potent compounds.…”
Section: Discussionmentioning
confidence: 99%
“…2a). In a series of papers, Wielens and Rhodes describe their application of (Saturation Transfer Difference) Nuclear Magnetic Resonance (STD-NMR), Surface Plasmon Resonance (SPR) and high resolution X-ray crystallography in a fragment-based screen for IN CCD binders [12][13][14].…”
Section: E2mentioning
confidence: 99%
See 2 more Smart Citations